2022
DOI: 10.2147/ijgm.s349624
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Defined Necroptosis-Related miRNAs Signature for Predicting the Prognosis of Colon Cancer

Abstract: This study aims at exploring the relationship between necroptosis-related miRNAs and colon cancer prognosis. Methods: We downloaded the miRNA sequencing data from the TCGA, and eight differentially expressed necroptosis-related miRNAs were screened. Then, we used Cox regression analysis to establish a prediction model of necroptosis-related miRNA. Finally, the prognosis related miRNAs were used to predict the target genes, and functional analysis was used to explore the potential mechanism of these target gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 54 publications
0
10
1
Order By: Relevance
“…Its area under the ROC curve (AUC) for 1-year, 3-year and 5-year OS were 0.697, 0.711, and 0.737 ( Figure 3E ), respectively. The AUC for predicting 5-year OS is better than those reported by Huang et al (AUC = 0.724) ( Huang et al, 2021 ), Yang et al (AUC = 0.656) ( Yang et al, 2022 ), and Liu et al (AUC = 0.639) ( Liu et al, 2022 ). The 7-NRGs based risk score model was further validated in the independent GEO dataset (GSE39582).…”
Section: Resultscontrasting
confidence: 65%
See 1 more Smart Citation
“…Its area under the ROC curve (AUC) for 1-year, 3-year and 5-year OS were 0.697, 0.711, and 0.737 ( Figure 3E ), respectively. The AUC for predicting 5-year OS is better than those reported by Huang et al (AUC = 0.724) ( Huang et al, 2021 ), Yang et al (AUC = 0.656) ( Yang et al, 2022 ), and Liu et al (AUC = 0.639) ( Liu et al, 2022 ). The 7-NRGs based risk score model was further validated in the independent GEO dataset (GSE39582).…”
Section: Resultscontrasting
confidence: 65%
“…For example, Huang et al found that a necroptosis-related miRNA risk signature consisting of seven miRNAs could be used to predict the prognosis of colon cancer patients ( Huang et al, 2021 ). Subsequently, Yang et al constructed a necroptosis-related miRNA signature for predicting colon cancer prognosis ( Yang et al, 2022 ). Later on, Liu et al proposed another model to predict the prognosis of colon cancer patients based on necroptosis-related lncRNAs( Liu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Upon further research, we found that LINC00052 was mostly located in the cytoplasm and highly expressed in HNSCC tissues with poor prognosis, in line with past studies. hsa-miR-148a-3p, whose family has already been proven to be biomarkers closely related to hepatocellular carcinoma (HCC) 36 , colon adenocarcinoma (COAD) 37 , acute myeloid leukemia (AML) 38 , esophageal squamous cell carcinoma (ESCC) 39 and gastric cancer (GC) 40 , is directly linked to vascular invasion. Ashizawa et al indicated that Overexpression 41 .…”
Section: High Plau Expression May Be Related To the Tumor Immune Resp...mentioning
confidence: 99%
“…The time-dependent ROC curve was based on the area under the ROC curve (AUC) to evaluate the prognostic value of the biomarkers [29]. In this study, AUC values ranged from 0 to 1, with an AUC of 0.5 indicating that the model has no predictive value and AUC of 0.5-1 indicating superior to random guesses and potential predictability [30,31]. Univariate and multivariate Cox regression analyses were also performed to determine whether the risk features could serve as an independent biomarker of OS in BRCA.…”
Section: Prognostic Models Of Necroptosis-related Mirnasmentioning
confidence: 99%